2019
DOI: 10.1109/access.2019.2924946
|View full text |Cite
|
Sign up to set email alerts
|

Adding and Segmenting Educational Videos: Experiences of Teacher Users in an Educational Portal

Abstract: Educational portals are environments that provide student and teacher users access to a variety of learning objects, among which are the educational videos. However, searching for such videos can be time-consuming and unproductive if only general syntactic descriptions are considered. Thus, an architecture of an educational semantic portal prototype, AvaOne, was conceived, implemented, and evaluated. Four experts in user profile and interaction design participated in the heuristic evaluation of this portal, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…A popular approach was to extract topics, concepts, and keywords to compute the similarity to other videos. The use of ontologies and external knowledge bases was used particularly to extract concepts [24,25,40,206]. Some interesting approaches considered other characteristics such as video readability [111],…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A popular approach was to extract topics, concepts, and keywords to compute the similarity to other videos. The use of ontologies and external knowledge bases was used particularly to extract concepts [24,25,40,206]. Some interesting approaches considered other characteristics such as video readability [111],…”
Section: Discussionmentioning
confidence: 99%
“…The learners could receive recommendations of videos and also Web pages. Borges and Silveira [25] retrieved videos by analyzing the subject-object-predicate construction of the user query and searching keywords in a semantic graphic database.…”
Section: Recommender and Retrieval Systemsmentioning
confidence: 99%
“…In [4], Borges and Silveira exploit descriptors associated with metadata to improve students' searches in educational semantic portals on the web. In particular, they focus on educational videos and propose adding descriptive information to such resources once they have been properly segmented and associated with semantics for each segmented portion.…”
Section: Related Workmentioning
confidence: 99%
“…Although previous studies indicated one of the factors influencing the low engagement was the MOOC interfaces, little MOOC research has concerned about the issue of interface design on user experience [3], [6]. User experience refers to the complete psychological experiences of users when interacting with the product [7]- [10]. Good interface design can facilitate the communication between the users and the platform, and lead to higher user experience, thus increasing learners' satisfaction and completion of MOOCs; On another side, problems of interface design will cause the usage of inconvenience, and then badly influence the quality of user experience, thus reducing learners' completion of MOOCs [11], [12].…”
Section: Introductionmentioning
confidence: 99%